Evaluasi Kesesuaian Lahan untuk Komoditas Padi dengan Memanfaatkan Aplikasi Sistem Informasi Geografis (SIG) di Kabupaten Lombok Tengah - Fitriani Risti Fauzi; Sirajuddin Haji Abdullah; Asih Priyati (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2018)
Land suitability evaluation for agricultural commodity can be arranged based on land condition. Since every plants type have a spesific growth requirement that suitable with the region characteristic, to grow and rise optimally. The aim of this research was to determine level of suitability land for